CFD modeling for hydrogen removal by a passive autocatalytic recombiner in oxygen-deficient conditions - Jongtae Kim; Jaehoon Jung; Sang Ho Kim (Nuclear Engineering and Technology, 2025)
This study aims to assess whether a computational fluid dynamics (CFD) approach effectively simulates hydrogen recombination characteristics by a passive autocatalytic recombiners (PAR) under oxygen-rich and lean conditions. Two PAR models were evaluated: one based on hydrogen recombination correlation provided by the manufacturer and another on hydrogen and oxygen mass diffusion rates. In the THAI-1 project, the experiments using an AECL PAR were performed to evaluate hydrogen recombination characteristics under oxygen-rich and lean conditions. In the CFD simulation of the HR18 test where oxygen was in surplus, both models predicted well the recombination rates. However, in simulations of the HR21 test under oxygen-starved conditions, the correlation-based PAR model significantly differed from experimental results. Conversely, the mass diffusion-based PAR model, incorporating oxygen diffusion to the catalytic surface, demonstrated greater accuracy than the correlation-based PAR model even with the recombination efficiency parameter used in the AREVA PAR correlation. These findings highlight the critical role of oxygen diffusion rates to catalytic surfaces in influencing hydrogen recombination rates, particularly in oxygen-starved conditions.